To Evaluate The Clinical Aspects, And The Prognostic Factors Of Morbidity And Mortality Of Eclampsia - Firoz, Abu Zahed Md.; Islam, Md. Anwarul (Jour Med Resh and Health Sci, 2021)
Introduction: Pre-eclampsia is a leading cause of maternal morbidity and mortality. Substandard care is often present and many deaths are preventable. Eclampsia, a major neurological complication of pre-eclampsia, is defined by a convulsive manifestation and/or conscious-ness disorder occurring in a preeclampsia context and cannot be at-tributed to a pre-existing neurological problem. Objective: To Evaluate the Clinical Aspects, And the Prognostic Factors Of Morbidity and Mortality Of Eclampsia. Materials and Methods: This is a retrospective, descriptive and analytical study of all patients admitted for eclampsia from April 2020 to March 2021 in the multipurpose intensive care unit of the anesthesiology Dept. Shaheed Ziaur Rahman Medical College Hospital, Bogura, Bangladesh. The diagnosis of eclampsia was based on the occurrence of peripartum seizures in a woman whose history and examination revealed no other cause for the convulsion. We studied the clinical, therapeutic, evolutionary and prognostic factors of morbidity and mortality. Results: We collected 45 cases of eclampsia for 2502 deliveries in the study (incidence of 1.8%). The average age of the patients was 22.23 years. Primiparity was found in 25 patients (55.5%). Antenatal consultations were effective in 4 patients (8.8%). Conscious-ness was clear at admission in 38 patients (84.4%) and for one patient a Glasgow score <8 was reported (1.96%). Severe hypertension was observed in 27.4% of cases. A ventilation intubation of 03 days was required in one patient in 1.9% of cases. Caesarean was the mode of delivery in 56.8% of cases and vaginal delivery was performed in 43%of cases. General anesthesia was doing in 18 patients (72%) and spinal anesthesia was performed in 7 patients (28%). Maternal complications were represented by: Postpartum acute renal failure (13.3%), Hellp syndrome (11.1%), and coagulopathy (16.6%). Prematurity was found in 12 neonates (13.3%), perinatal mortality was 9.1% and the maternal mortality rate was 4.4%. Conclusion: Eclampsia is still responsible for high maternal and infant mortality. The association of two or even more serious factors is very important in this mortality.